The Complexity of the Language Level and the Multimodality Used in Singaporean and Indonesian Science Textbooks Written in English for Primary Three and Four - Ika Sari, Latifa; Soetopo, Djoko (English Education Journal, 2017)
Teaching Maritime English Vocabulary to cadets can be very challenging for an English teacher. Cadets have daily tight schedules and physical activities that often consume their energy. It is important for the teachers to find out a strategy that is effective to be implemented in the classroom. This research was aimed to investigate the effectiveness of Vocabulary Self-Collection Strategy (VSS) and Word Mapping Strategy (WMS) to teach Maritime English vocabulary of cadets with high and low metacognitive awareness. This study employed a quasi-experimental design with a 2x2 factorial design.Two experimental groups of the first year Nautical Cadetsof Semarang Merchant Marine Polytechnic were involved in this study. There were 36 participants.  Metacognitive Awareness Inventory and Maritime English Vocabulary Assessment were used as the instrument for collecting the data. Observation was also conducted to support the data findings. To analyze the data, Paired Sample T-test and Two Way ANOVA were used.The research findings showed that both VSS and WMS are effective to be used in teaching Maritime English Vocabulary to cadets with high and low metacognitive awareness. However, when we compared the effectiveness of VSS and WMS, the findings revealed that VSS was more effective to be used in both high and low metacognitively aware cadets.The statistical analysis showed that there is an interaction among vocabulary teaching strategies, metacognitive awareness and vocabulary mastery.